Whole-Slide Imaging (WSI) Versus Traditional Microscopy (TM) Through Evaluation of Parameters in Oral Histopathology: A Pilot Study - Islam Atikul; Banerjee Abhishek; Roy Bireswar; Chatterjee Kumarjyoti; Singhania Kumari N (Wolters Kluwer Medknow Publications, 2024)
Backgroundhistopathology plays a pivotal role in clinical diagnosis, research, and medical education. In recent years, whole slide imaging (wsi) has emerged as a potential alternative to traditional microscopy for pathological examination. This study aims to provide a comprehensive comparison of wsi and traditional microscopy(tm) in various aspects of histopathology practice. Materials and MethodsIn this study, total of 30 cases comprising of oral premalignant and malignant cases which were diagnostically challenging was considered from the archives of the institute for validation. The slides were scanned with slide scanner and were evaluated by histopathologists. The comparative parameters which were noted were diagnostic discordances, number of fields observed to reach the diagnosis and time taken. ResultsThe mean time taken by the pathologists to reach the diagnosis was significantly less in whole slide imaging technique. The average number of fields observed was higher by using wsi that too in a lesser time compared to tm, the results were found to be statistically significant with p=0.001.however the diagnostic disparity were seen to be maximum for verrucous lesions both in wsi and tm. Conclusionwsi has facilitated the specialty with rapid mode of diagnosis in a more efficient and error less manner. It has also aided in case banking as well as research possibilities. Hence with the advent of telepathology it is very much necessary to get trained with wsi as early as possible so that the professionals can render correct diagnosis.